Accessory and cavitated uterine mass: A rare cause of dysmenorrhea and chronic pelvic pain (Indian Journal of Case Reports, 2022)
Accessory and cavitated uterine mass (ACUM) is a rare developmental uterine anomaly that is said to develop due to duplication of ductal Mullerian tissue. It is an accessory cavity lying along the lateral wall of the uterus near the site of attachment of the round ligament and presents in young females with pelvic pain and dysmenorrhea. Histologically, the cavity is lined with endometrium and smooth muscle bundles similar to the myometrium. Ultrasound is helpful in the identification of the lesion. MRI of the pelvis is the imaging modality of choice for diagnosis. Laparoscopy and histopathology remain confirmatory. This report describes a case of ACUM in a young female who was managed by surgical excision of the mass.